Pengaruh Efikasi Diri Terhadap Kemampuan Pemecahan Masalah Matematika Kelas X MA NW Putri Narmada Tahun Ajaran 2021/2022 - Hilyana Zilfit; Muhammad Turmuzi; Wahidaturrahmi Wahidaturrahmi; Baidowi Baidowi (Griya Journal of Mathematics Education and Application, 2023)
This study aims to determine the effect of self-efficacy on problem-solving abilities. The benefits of research for researchers are as an exercise in carrying out scientific research and for teachers, it is to increase the self-efficacy of students in the classroom so that they can improve problem-solving abilities. This research was a type of quantitative research using simple linear regression analysis techniques. This research was carried out at MA NW Putri Narmada for the 2021/2022 academic year. With a population of all class X MA NW Putri Narmada and a sample of 61 students. The data collection instrument used questionnaires and tests. Questionnaires were used to obtain data about students' self-efficacy, while tests were used to obtain data about students' mathematical problem-solving abilities. The results showed that self-efficacy had an effect on the mathematical problem-solving ability of students of class X MA NW Putri Narmada with an effect of 30.3%, while the level of self-efficacy relationship with mathematical problem-solving skills was 0.55 with a moderate level of relationship. student learning, the more knowledge the student has and the better the mathematical problem-solving ability of the student, so students who have high self-efficacy will be more diligent and enthusiastic in learning.